Sustainable education: Analyzing the determinants of university student dropout by nonlinear panel data models - Kim, Donggeun; Kim, Seoyong (Sustainability (Switzerland), 2018)
University dropout is a serious problem. It affects not only the individual who drops out but also the university and society. However, most previous studies have focused only on the subjective/individual level. University dropout is a very important issue in South Korea, but it has not received much research attention so far. This study examined the possible causes of university dropout in South Korea at the aggregate level, focusing on four fundamental categories: students, resources, faculty, and university characteristics. Three-year balanced panel data from 2013 to 2015 were constructed and estimated by using nonlinear panel data models. The findings show that cost and burden for students, financial resources, qualitative and quantitative features of faculty, and type/size of the university have significant effects on university dropout.
Keywords: Determinants of dropout; Dropout; Sustainable education; University student; Withdrawal